Predicting microfinance loan default - Kumar, Senthil; Aslam, Mohammad (2021)
Microfinance lending institutions can use the following predictors to avoid bad loans : Marital status (single individuals are more prone to defaults). Time period of loan (longer loans are prone to higher default rate). Interest rate (very high interest rates are likely to resul in loan default).